2020
DOI: 10.1155/2020/3860936
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Indexes Can Be Used to Predict the Incidence of Hypothyroidism in Nasopharyngeal Carcinoma Patients after Radiotherapy

Abstract: Background. This study explored the relationship between thyroid-associated antibodies, immune cells, and hypothyroidism to establish a predictive model for the incidence of hypothyroidism in patients with nasopharyngeal carcinoma (NPC) after radiotherapy. Methods. A total of 170 patients with NPC treated at the Cancer Hospital of University of Chinese Academy of Sciences between January 2015 and August 2018 were included. The complete blood count, biochemical, coagulation function, immune cells, and thyroid-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Hypothyroidism is a common complication of radiotherapy for NPC. In the present study, we found that the incidence of hypothyroidism after radiotherapy for nasopharyngeal cancer was 38%, which was similar to that reported by other authors, 11 who reported a primary hypothyroidism incidence of 45.29% (77/170). After baseline matching, both disease‐free survival and recurrence‐free survival rates were higher in the hypothyroid group than in the group with normal thyroid function.…”
Section: Discussionsupporting
confidence: 92%
“…Hypothyroidism is a common complication of radiotherapy for NPC. In the present study, we found that the incidence of hypothyroidism after radiotherapy for nasopharyngeal cancer was 38%, which was similar to that reported by other authors, 11 who reported a primary hypothyroidism incidence of 45.29% (77/170). After baseline matching, both disease‐free survival and recurrence‐free survival rates were higher in the hypothyroid group than in the group with normal thyroid function.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, thyroid autoantibodies, particularly TGAb, could be an expression of a more general maternal immune system abnormality leading to RPL (45). Research has shown that a positive TGAb and TPOAb expression is also associated with a higher incidence of hypothyroidism (46), with the presence of TPOAb being linked to RPL (47). Therefore, TAI and the thyroid function may have significant implications for the pathophysiology of RPL.…”
Section: Discussionmentioning
confidence: 99%
“…NPC is causally linked to Epstein-Barr virus (EBV) infections ( 4 , 5 ). The 5-year overall survival rate for NPC is above 80% ( 6 , 7 ). However, recurrence occurs in 10% to 15% of patients with NPC, and the 5-year overall survival rate for patients with recurrent NPC is only 13.2% to 38% ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%